(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Concrete is most widely used material in civil engineering for the construction of different structure in the world. The continuous researches are carried out in this field with reference to mechanical properties as well as chemical reactions. Which result in High Strength Concrete (HSC), Self Compacting Concrete (SCC), High Performance Concrete (HPC), and Fiber Reinforced Concrete? The partial replacement of cement is made on the trial bases with Fly Ash (FA), Ground Granulated Blast Furnace Slag (GGBS) And Condensed Silica Flume (CSF). In this present experimental investigation, the Ordinary Portland cement (OPC) is partially replaced by Flay ash and Ground granulated blast furnace slag (GGBS) for a mix design of M20 grade without affecting on its strength.